Radiation Effects on Aluminosilicate Optical Fibers: Spectral Investigations From the Ultraviolet to Near‐Infrared Domains. Issue 3 (10th September 2018) - Alessi, Antonino; Guttilla, Angela; Girard, Sylvain; Agnello, Simonpietro; Cannas, Marco; Robin, Thierry; Boukenter, Aziz; Ouerdane, Youcef
Abstract : Online X‐ray radiation induced attenuation (RIA) has been performed in aluminosilicate optical fibers having different Al concentrations. The studied UV‐visible spectral range revealed the presence of absorption bands related to Al defects. Their generation is shown to be not noticeably dependent on the dose rate. Furthermore, the Al content (2–4 wt%), the core sizes, and the manufacturing processes (SPCVD or MCVD) of the preforms have no significant influence on the RIA levels and kinetics, as well as the drawing parameters within the range used for specialty fiber production. The Aluminum–Oxygen Hole Center (Al–OHC) presence was proved by their 2.3 eV absorption band and by their electron paramagnetic resonance (EPR) signature. The growth kinetic of their concentration versus dose is linear up to 2–3 kGy (SiO2 ). While, at higher doses, EPR data highlight a saturation, suggesting that the Al–OHC generation results from a process involving precursors. To explain the E'Si growth kinetic with the dose, two processes are necessary, the first is from precursors and the second by breaking SiOSi links. The study of the RIA induced in the NIR demonstrates that the tail of the 2.3 eV Al–OHC band cannot explain the fiber degradation and that additional defects contribute to the induced losses. Abstract : Online radiation induced attenuation is studied in aluminosilicate optical fibers and the absorption of the aluminum–oxygen hole centers (Al–OHC) is highlighted. Their generation, confirmed by electron paramagnetic resonance, is not noticeably dependent on the dose rate, Al content, core sizes, and manufacturing processes. This study shows that the 2.3 eV absorption band of the Al–OHC cannot explain the attenuation in the near‐infrared.